Analisis Problematika Penetapan Wali Nikah dan Solusinya dalam Praktik Kantor Urusan Agama: Analysis of the Problems of Determining Marriage Guardians and Their Solutions in Practice at the Office of Religious Affairs - Lista Putri Aulia; Riza Aisyah; Keysa Shadira; Nur Rahma Aulia; Edi Suresman (DIRASAH: Jurnal Kajian Islam, 2026)
The determination of marriage guardians is a crucial aspect of marriage implementation because it constitutes one of the legal requirements for a valid marriage contract in Islamic law. In practice at the Office of Religious Affairs (KUA), the process of determining marriage guardians often encounters various administrative, social, and religious challenges. This study aims to analyze the forms of problems arising in the determination of marriage guardians and to identify solutions that can be applied to address them. This research uses a qualitative approach through literature study and conceptual analysis of regulations and field practices. The findings indicate that common problems include the absence of a biological guardian, unclear guardian status, guardians who do not meet legal requirements, and family conflicts that hinder the determination process. In addition, limited public understanding of marriage guardian regulations is also a significant obstacle. These problems are influenced by cultural factors and ineffective family communication. Solutions include optimizing the role of marriage registrars, increasing public education on marriage law, and implementing proper procedures for appointing a judge guardian. Therefore, stronger cooperation between KUA and the community is needed to ensure that the determination of marriage guardians is carried out effectively, orderly, and in accordance with applicable regulations.